Model reduction based on limited time interval impulse response gramians - Kumar, Deepak; Haja Mohideen, Ahmad Jazlan; Sreeram, Venkatappa (Institute of Electrical and Electronics Engineers Inc., 2018)
— This paper presents a new limited time interval impulse response Gramians (LTIRG) based model reduction method for single-input single-output (SISO) continuous-time systems. The proposed approach incorporates the time-interval Gramians with impulse response Gramians to preserve the input-output behaviour of the original system for the specified time interval. A numerical example is given to illustrate the proposed approach, and the results are compared with the standard techniques.